2006
DOI: 10.1149/1.2161453
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Sodium Salt Coating on a Graphite Negative Electrode for Lithium-Ion Batteries

Abstract: The electrochemical performance of a graphite electrode for rechargeable lithium-ion batteries was successfully enhanced by pretreatment of graphite powders with NaCl and Na 2 CO 3 aqueous solutions. The procedure of the pretreatment is simple and easy, that is, graphite powders are dispersed in the aqueous solutions, and then filtered and dried. Since the surface of the graphite powder was modified with a sodium salt coating, the irreversible capacity at the initial cycle was suppressed by the pretreatment wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 24 publications
3
24
0
Order By: Relevance
“…However, among electrodes employing either of the water‐soluble binders, CMC‐Na or PAA‐Na, there was no notable difference in the coulombic efficiency. This is an indication that the merits of using PAA‐Na‐containing graphite electrodes, as reported previously, are dependent on the amount of binder applied and do not necessarily lead to improvements if used in practical amounts. This is reflected in the electrochemical results for the full‐cell cycling against a commercial LiFePO 4 positive electrode, for which the CMCSBR composites yielded the highest capacity retention after 100 cycles.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…However, among electrodes employing either of the water‐soluble binders, CMC‐Na or PAA‐Na, there was no notable difference in the coulombic efficiency. This is an indication that the merits of using PAA‐Na‐containing graphite electrodes, as reported previously, are dependent on the amount of binder applied and do not necessarily lead to improvements if used in practical amounts. This is reflected in the electrochemical results for the full‐cell cycling against a commercial LiFePO 4 positive electrode, for which the CMCSBR composites yielded the highest capacity retention after 100 cycles.…”
Section: Discussionsupporting
confidence: 66%
“…Experiments with laboratory-scale electrodes demonstrated that water-processed electrode formulations could consistently achieve higher coulombic efficiencies than the polyvinylidene difluoride (PVdF) composites.H owever, among electrodes employinge ither of the water-soluble binders, CMC-Na or PA A-Na, there was no notable difference in the coulombic efficiency.T his is an indication thatt he meritso f using PA A-Na-containing graphite electrodes,a sr eported previously, [22,60] are dependento nt he amount of binder applied and do not necessarily lead to improvements if used in practical amounts.T his is reflected in the electrochemical results for the full-cell cycling against ac ommercial LiFePO 4 positive electrode, for which the CMCSBR composites yielded the highest capacity retention after 100 cycles. This is in stark contrast to the trends observed in alloying materials, such as silicon, for which bindersa re generally employedi n Figure 7.…”
Section: Discussionmentioning
confidence: 78%
“…It has been reported that the presence of sodium salts has beneficial effects on the SEI layer formation and improves the overall electrode performance. ,, Furthermore, Nguyen et al proposed HF scavenging in the presence of −COONa groups, since CMC-Na and PAA-Na carry sodium ions into the cell. El Ouatani et al and Komaba et al concluded that the ions are readily exchanged by lithium ions in contact with the electrolyte.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, the formation of sodium salts during the SEI layer formation has previously been shown to lead to improved cycle life in the case of graphite electrodes. 31,65,66 ■ CONCLUSIONS Water-processed graphite electrodes employing either 4 wt % of CMC-Na:SBR, PAA-Na, or CMC-Na:PAA-Na were cycled in graphite:LiFePO 4 full cells (ca. 65 mAh) and analyzed by photoelectron spectroscopy (PES), using an in-house and a synchrotron light source (1486.6 and 2300 eV, respectively).…”
Section: Acs Applied Energy Materialsmentioning
confidence: 99%
“…Further deconvolution of the O 1s, Na 1s, and C 1s peaks reveals the presence of sodium carbonate on the surface. Previously, surface coating of Na 2 CO 3 on the graphite anode in lithium‐ion batteries and on P2‐Na x MO 2 in sodium‐ion batteries has been shown to improve cell cycling by forming an artificial SEI layer and supplying additional Na source. On the other hand, the carbon surface is also rich in carbon–oxygen functional groups (after excluding O in the carbonate), which have been reported to enhance the cycling capacities of biomass‐derived carbon in sodium‐ion batteries through redox reaction with Na ions …”
Section: Resultsmentioning
confidence: 99%